Environmental trade-offs and policy recommendations for livestock intensification in the Northwest Highlands of Vietnam - Dao, Thi Thu Hang; Mwema, Emmanuel; Notenbaert, An Maria Omer; Atieno, Mary (International Livestock Research Institute, 2024)
The Northwest Highlands (NWH) of Vietnam have great potential for livestock development because of their favorable climate and strategic proximity to China, a major consumer of meat products from Vietnam. Despite this potential, livestock farming in the region remains small-scale, with challenges including low-quality breeds, inadequate feed sources, and limited land for grazing and pastures alongside environmental pressure. The SAPLING initiative in Mai Son District, Son La Province is addressing these challenges by promoting innovations in improved feeds, forages, animal genetics, herd health, and livestock value chains.